Learning across Generations in Europe: Contemporary Issues in Older Adult Education - Schmidt-Hertha, Bernhard; Krašovec, Sabina Jelenc; Formosa, Marvin (Research on the education and learning of adults, 2014)
FREELY AVAILABLE ONLINE AS OPEN ACCESS BOOK! Learning across Generations in Europe: Contemporary issues in older adult education constitutes an important book in the emergent field of study of older adult learning. The book gives a clear and wide overview on the different concepts, ideas, and meanings, related to older adults' education, learning and intergenerational learning through strong theoretical standpoints, empirical research, and policy directions. The field of older adult education has expanded immensely in recent years since it raised questions that are connected to a rapidly ageing society in very turbulent times of economic and social changes in Europe. This book provides the basis for an in-depth analysis of the understandings and interpretations of education and learning in later-life, rethinking the development of different approaches for education of older adults, as well as diverse research and evaluation of different forms of older adults' education and learning. It brings together both orthodox approaches to educational gerontology and older adult learning on important emerging issues faced by educators around the globe. The chapters address the contemporary differentiated discussion on diverse phenomena labelled ranging from intergenerational learning to older men learning, providing robust impulses for the development of further theoretical and empirical research on older adult and intergenerational learning. It is the editors' intention that this collection of papers acts as a persuasive argument for formal and non-formal learning agencies to open more doors for older adults.